Knee Cell-Based Cartilage Restoration - Pickett, Adam M.; Hensley, Dana T., Jr. (The Journal of Knee Surgery, 2019)
As our patients become more physically active at all ages, the incidence of injuries to articular cartilage is increasing causing significant pain and disability. The intrinsic healing response of articular cartilage is poor because of its limited vascular supply and capacity for chondrocyte division. Nonsurgical management for the focal cartilage lesion is successful in the majority of patients. Those patients who fail conservative management may be candidates for a cartilage reparative or reconstructive procedure. The type of treatment available depends on a multitude of lesion-specific and patient-specific variables. First-line therapies for isolated cartilage lesions have demonstrated good clinical results in the correct patient, but typically repair cartilage with fibrocartilage, which has inferior stiffness, inferior resilience, and poorer wear characteristics. Advances in cell-based cartilage restoration have provided the surgeon a means to address focal cartilage lesions utilizing mesenchymal stem cells, chondrocytes, and biomimetic scaffolds to restore hyaline cartilage.
Keywords: cartilage; chondrocyte; matrix; scaffold; articulated